2007
DOI: 10.1128/mcb.00467-07
|View full text |Cite
|
Sign up to set email alerts
|

c-Cbl-Mediated Regulation of LAT-Nucleated Signaling Complexes

Abstract: The engagement of the T-cell receptor (TCR) causes the rapid recruitment of multiple signaling molecules into clusters with the TCR. Upon receptor activation, the adapters LAT and SLP-76, visualized as chimeric proteins tagged with yellow fluorescent protein, transiently associate with and then rapidly dissociate from the TCR. Previously, we demonstrated that after recruitment into signaling clusters, SLP-76 is endocytosed in vesicles via a lipid raft-dependent pathway that requires the interaction of the endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
138
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(146 citation statements)
references
References 54 publications
8
138
0
Order By: Relevance
“…In addition, consistent with its role as an E3-ubiquitin ligase in several signaling systems, c-Cbl has been implicated in ubiquitylation of the TCRz and CD3d chains of the TCR as well as the signaling proteins ZAP-70, LAT, PLC-g1, PI3K, Vav, and PKC-u in T cells (Weissman 2001;Duan et al 2004;Balagopalan et al 2007). The effects of LATubiquitylation on controlling internalization and cellular LAT levels are discussed in the imaging section later.…”
Section: Plc-g1 Binds Y132 Of Lat and Mediates Transcriptional Activamentioning
confidence: 86%
See 4 more Smart Citations
“…In addition, consistent with its role as an E3-ubiquitin ligase in several signaling systems, c-Cbl has been implicated in ubiquitylation of the TCRz and CD3d chains of the TCR as well as the signaling proteins ZAP-70, LAT, PLC-g1, PI3K, Vav, and PKC-u in T cells (Weissman 2001;Duan et al 2004;Balagopalan et al 2007). The effects of LATubiquitylation on controlling internalization and cellular LAT levels are discussed in the imaging section later.…”
Section: Plc-g1 Binds Y132 Of Lat and Mediates Transcriptional Activamentioning
confidence: 86%
“…Microclusters play a predominant role in the generation of sustained signals. Current models also indicate that cluster centralization plays an important role in signal termination and that the cSMAC is a site both for TCR down-regulation yet also for amplification of weak signals (Lee et al 2003;Mossman et al 2005;Varma et al 2006;Balagopalan et al 2007;Cemerski et al 2008;Nguyen et al 2008). A recent study using a photoactivatable agonist in a lipid bilayer system has provided even greater precision in the temporal resolution of these events and demonstrated that adapters are recruited to microclusters within four seconds (Huse et al 2007).…”
Section: Lat Microclusters: Sites Of Nucleation Of Signaling Complexesmentioning
confidence: 99%
See 3 more Smart Citations